Culture, history, and Bakpia Pathok processing method as a gastronomic tourist attraction in Yogyakarta - Mulyantari, Enny; Hasnah, Vivin Afanin; Nugroho, Setyo Prasiyono (Technium Social Sciences Journal, 2023)
The aims of this study are to determine the culture, history, and method of "Bakpia Pathok 25" making process and analyze its gastronomy tourism potential as a culinary tourist attraction in Malioboro, Yogyakarta. This research applied a qualitative method. The study population in this research is limited to Bakpia Pathok 25 which is only located in Kampung Pathuk for its well-known reputation in Yogyakarta, providing direct testers to tourists and allowing researchers to observe Bakpia making process directly. Purposive sampling was used as the data collection technique, with eleven informants consisting of gastronomy experts, historians, owners or managers, and employees of Bakpia Pathok 25, tourists, and the local communities. The sampling technique used for this research was the interview, observation, and documentation. SWOT Analysis is used as the data analysis to get an overview of internal and external factors influencing Bakpia Pathok 25 as a gastronomic tourism potential and culinary tourist attraction. The study results show that the history of Bakpia Pathok 25 is a typical Chinese food called "Tou Luk Pia" which is then interpreted as green bean pia cake. The Chinese then brought this food to Indonesia in the 1948s. The manufacturing method implemented in Bakpia Pathok 25 processing uses the Dry Food Processing Technique, namely the Baking method. The culture of "Bakpia Pathok 25 Bakpia is a form of food acculturation in the culinary field between the Indonesian and the Chinese people. By producing bakpia, merti bakpia procession is held as a form of gratitude from Pathuk people for abundant sustenance.